Brotherhood and Inheritance : a Canonical Reading of the Esau and Edom Traditions. - Anderson, Bradford A. (Library of Hebrew Bible/Old Testament studies., 2012)
This study offers a canonical reading of the Esau and Edom traditions, examining the portrayal of Esau and Edom in Genesis, Deuteronomy, and the prophetic material. First, it is argued that the depiction of Esau and his descendants in Genesis and Deuteronomy is, on the whole, positive. Second, it is put forward that Edom is portrayed negatively by the prophets for violating their kin, and for disrespecting the divine apportioning of the lands. Finally, it is suggested that these traditions have resonance with one another based on recurring literary and theological motifs, heuristically framed.